UV resistance of polystyrene co-butyl acrylate (PSBA) encapsulated lignin–saponite nanohybrid composite film. (15th January 2016) - Jairam, Suguna; Bucklin, Ray; Correll, Melanie; Sakthivel, Tamil Selvan; Seal, Sudipta; Truett, John; Tong, Zhaohui
Abstract: Protecting biological systems and organic materials from high ultraviolet (UV) radiation is a significant issue for engineering materials in both terrestrial and space applications. In this study, the synthesized composites of polystyrene butyl acrylate (PSBA) encapsulated lignin based nanohybrid were evaluated as UV resistant cladding materials for both applications. The UV transmittance of the composite films and their physical, thermal, and chemical degradation after prolonged exposure to high UV radiation (10 Earth days and 30 Mars equivalent days) at low temperatures of 3.4 °C were examined. The results showed that the composite films blocked the UV radiation and there was no significant effect of UV radiation on film integrity, mechanical and thermal properties of the composite films when they were exposed to high intensity UV radiation (132 W/m 2 ) within 24 h. Further, FTIR spectra of the composite films before and after UV radiation demonstrated that the films did not have notable oxidation degradation, although the glass transition temperature was slightly decreased with increased exposure time. Graphical abstract: Highlights: The lignin-based nanocomposite films block 98% of UV transmittance. The film was under UV radiation that is 10 times stronger than that on Earth. The mechanical properties of the films were kept under 24-h UV radiation. Slight thermal degradation was detected under 24-h UV radiation.